Effects of Nicotinamide Riboside Supplementation on Postmortem Mitochondrial Functionality and Apoptotic Activation - Chen Zhu; Luke A. Whitcomb; Adam J. Chicco; Morgan E. Gravely; Hanna M. Alcocer; Daniela A. Alambarrio; John M. Gonzalez; Colton L. Smith; Mahesh N. Nair; Huey Yi Loh; Terry E. Engle; Arya Niraula; et al. (Metabolites)
Background/Objectives: Early postmortem mitochondrial function and apoptotic activation affect meat quality development. Nicotinamide riboside (NR) supplementation to pigs prior to harvest can improve pork color stability, but its mechanism remains unclear. This study aimed to evaluate the impact of NR supplementation on early postmortem mitochondrial functionality and apoptosis. Methods: Sixteen pigs (N = 16) were individually fed a control or NR-supplemented diet (30 mg·kg body weight−1·d−1) for 10 days prior to harvest. Longissimus dorsi muscle samples were collected at 45 min and 24 h postmortem and analyzed for mitochondrial functionality using high-resolution respirometry and apoptotic protein abundance (apoptosis regulator Bcl-2-associated X (BAX), apoptotic inducing factor (AIF), and caspase 3 (CASP3)) via immunoblotting. Results: NR-supplemented muscle exhibited lower proton leak-associated respiration at 45 min postmortem (p < 0.05), followed by a slower accumulation of mitochondrial outer membrane permeabilization (MOMP; p < 0.05) and a slower loss of mitochondrial integral function (p < 0.05) from 45 min to 24 h postmortem. NR supplementation decreased BAX abundance at 45 min postmortem but increased mature AIF abundance (62 kDa) at 24 h postmortem (p < 0.05). The abundance of CASP3 fragments (~29 kDa) decreased from 45 min to 24 h postmortem, independent of treatment (p < 0.05). Conclusions: NR supplementation demonstrated the potential to protect mitochondrial integral function and alleviate apoptotic activation in early postmortem porcine skeletal muscle, which might contribute to a higher meat color stability in NR-supplemented pork during retail display.